The two-obstacle problem for the parabolic biharmonic equation. (May 2016) - Novaga, Matteo; Okabe, Shinya
Abstract: We consider a two-obstacle problem for the parabolic biharmonic equation in a bounded domain. We prove long time existence of solutions via an implicit time discretization scheme, and we investigate the regularity properties of solutions.